Epigenetic Regulation by Chromatin Activation Mark H3K4me3 in Primate Progenitor Cells within Adult Neurogenic Niche - Sandstrom, Richard S. (Nature Publishing Group, 2014)
Histone 3 lysine 4 trimethylation (H3K4me3) is known to be associated with transcriptionally active or poised genes and required for postnatal neurogenesis within the subventricular zone (SVZ) in the rodent model. Previous comparisons have shown significant correlation between baboon (Papio anubis) and human brain. In this study, we demonstrate that chromatin activation mark H3K4me3 is present in undifferentiated progenitor cells within the SVZ of adult baboon brain. To identify the targets and regulatory role of H3K4me3 within the baboon SVZ, we developed a technique to purify undifferentiated SVZ cells while preserving the endogenous nature without introducing culture artifact to maintain the in vivo chromatin state for genome-wide studies (ChIP-Seq and RNA-Seq). Overall, H3K4me3 is significantly enriched for genes involved in cell cycle, metabolism, protein synthesis, signaling pathways, and cancer mechanisms. Additionally, we found elevated levels of H3K4me3 in the MRI-classified SVZ-associated Glioblastoma Multiforme (GBM), which has a transcriptional profile that reflects the H3K4me3 modifications in the undifferentiated progenitor cells of the baboon SVZ. Our findings highlight the importance of H3K4me3 in coordinating distinct networks and pathways for life-long neurogenesis, and suggest that subtypes of GBM could occur, at least in part, due to aberrant H3K4me3 epigenetic regulation.